2015
DOI: 10.1002/per.1981
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity and Social Justice: Effect of Individual Differences in Justice Sensitivity on Solidarity Behaviour

Abstract: We investigate the effect of individual differences in justice sensitivity (JS) on giving behaviour in a solidarity game, its potential moderators and the underlying psychological mechanisms. In a solidarity game, subjects are asked to make decisions about transferring money to other players in a case in which they win a random draw and the other players lose. The results of four studies showed the following: (1) JS explains a unique portion of variance in the solidarity behaviour, above and beyond other basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…For example, Van Prooijen and Kerpershoek ( 2013 ) found that participants with an unfulfilled basic psychological need for autonomy showed increased punishment intentions towards a perpetrator, and explained these results by arguing that their autonomy-deprived participants had an increased concern for justice. However, the need for autonomy might have also been fulfilled by compensatory actions, as the concern for justice is related to compensation, as well (Lotz et al 2013 ; Stavrova and Schlösser 2015 ). Hence, it is not necessarily the case which the autonomy-deprived people are more punitive; they might be more motivated to restore justice in general.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Van Prooijen and Kerpershoek ( 2013 ) found that participants with an unfulfilled basic psychological need for autonomy showed increased punishment intentions towards a perpetrator, and explained these results by arguing that their autonomy-deprived participants had an increased concern for justice. However, the need for autonomy might have also been fulfilled by compensatory actions, as the concern for justice is related to compensation, as well (Lotz et al 2013 ; Stavrova and Schlösser 2015 ). Hence, it is not necessarily the case which the autonomy-deprived people are more punitive; they might be more motivated to restore justice in general.…”
Section: Discussionmentioning
confidence: 99%
“…Morgan et al (2017) successfully measured gratitude motivation and found that it added uniquely to their ability to account for individual well-being. The justice sensitivity scales are trait measures of emotional responses to injustice, and extensive research documents the relationships among these scales and a variety of relevant constructs, such as solidarity with disadvantaged others (Gollwitzer et al, 2005); perceived procedural injustice, anger, political protest against injustice, well-being, and prosocial behavior (Gollwitzer et al, 2009; Lotz et al, 2013; Rothmund et al, 2014; Stavrova & Schlösser, 2015); and behavioral outcomes in economic games (Edele et al, 2013; Lotz et al, 2011). In addition, Fowers, Lang, et al (2020) found that the motivational aspects of trait fairness and trait kindness constituted latent variables that were distinct from virtue-related behavior and disposition in an experience-sampling study.…”
Section: The Strive-4 Model Research Agendamentioning
confidence: 99%
“…For instance, existing measures assess positive emotions towards the group (Dragojevic & Giles, 2014;Wheeless, 1976), identification with the group (Doosje, Ellemers, & Spears, 1995;Leach et al, 2008;Wiley et al, 2013), and beliefs that the ingroup and outgroup should "stick together" (Glasford & Calcagno, 2012, Study 1). Other measures relate to various forms of support, such as prosocial attitudes towards the outgroup (Stavrova & Schlösser, 2015;Vollhardt et al, 2016), expressions of support for resolving the outgroup's cause (Cortland et al, 2017), empathic concern towards the outgroup (Papacostas, 2012), and collective action intentions to help address the outgroup's cause (Chayinska, Minescu, & McGarty, 2017;Dixon et al, 2017;Glasford & Calcagno, 2012, Study 2;Saab, Tausch, Spears, & Cheung, 2015;Subašić, Schmitt, & Reynolds, 2011). A notable exception to the uni-or bi-dimensional measurement of solidarity comes from Smith, McGarty, and Thomas (2018), who assessed Twitter users' solidarity with refugees by coding the proportion of their tweets that communicated pro-refugee sentiment, affiliation, loyalty, and collective action.…”
Section: The Case For a Measure Of Political Solidaritymentioning
confidence: 99%